THE FUNCTIONING OF LANGUAGE IDEOLOGIES IN IVANOFRANKIVSK (BASED ON THE MATERIAL OF THE POLISH LANGUAGE AS THE LANGUAGE OF A NATIONAL MINORITY) - Pelekhata, Olena (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article presents an analysis of the functioning of linguistic ideologies in the city on the basis of Polish as a national minority language. The material for the study is represented by recorded interviews with residents of the oldest generation.The history of the city confirms the fact that attitudes towards language are an obvious link between language ideologies and human behaviour. Language ideologies are tools that assign a certain value to languages on the basis of ethnicity, state or social affiliation.Language ideologies have led to the disappearance of the transmission of Polish from parents to children, and then to the gradual resumption of this process in local Polish families. The oldest generation of local Poles lived in three different socio-historical periods. Each of them influenced the change of language ideologies. The fear of using Polish led to the almost complete elimination of Polish among the older generation, who are actually the children of the oldest generation.